The PENGARUH EKONOMI DAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PENINGKATAN PERKARA PERCERAIAN DI KOTA BATAM PADA TAHUN 2022: PENGARUH EKONOMI DAN KEKERASAN DALAM RUMAH TANGGA TERHADAP PENINGKATAN PERKARA PERCERAIAN DI KOTA BATAM PADA TAHUN 2022 - Faradiba Jabnabillah (JURNAL SINTAK, 2023)
Divorce is the breaking of the marriage bond caused by several factors such as the economy and domestic violence. Therefore the authors are interested in conducting research to find out how much influence the economy and domestic violence have on the increase in divorce cases in the city of Batam. The research method used is a quantitative method with data collection techniques, namely secondary data from the Batam District Court. The classical assumption test and hypothesis test were carried out. The data analysis method was performed using multiple linear regression statistical tests. Based on the data analysis that has been done, it is known that the economy and domestic violence simultaneously affect the increase in divorce. But the economy partially does not affect the increase in divorce. Keywords: Economy; Domestic violence; Divorce